2019
DOI: 10.1111/geer.12175
|View full text |Cite
|
Sign up to set email alerts
|

The Productivity Effects of Worker Mobility Between Heterogeneous Firms

Abstract: We analyze the effect of worker inflows on establishments’ productivity, using German data. Previous studies for other countries have found positive effects of hiring workers from superior (more productive or higher paying) firms. Ranking establishments by their median wage, we find that inflows from inferior establishments seem to increase hiring establishments’ productivity. Further empirical analyses suggest our findings are due to a positive selection of such inflows from their sending establishments. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…When we examined positive and negative productivity gap separately, we have shown that hiring workers from more productive companies is beneficial, however, hiring from less productive one in not harmful, which is consistent with the idea that employees apply the knowledge of better operations. These results are consistent with previous finding of Stoyanov & Zubanov (2012) and contradicts Stockinger & Wolf (2016). One can also note that our measure of productivity gap is composed of two parts: the magnitude of incoming workers, and the superiority of the firm they are coming from in terms of productivity.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…When we examined positive and negative productivity gap separately, we have shown that hiring workers from more productive companies is beneficial, however, hiring from less productive one in not harmful, which is consistent with the idea that employees apply the knowledge of better operations. These results are consistent with previous finding of Stoyanov & Zubanov (2012) and contradicts Stockinger & Wolf (2016). One can also note that our measure of productivity gap is composed of two parts: the magnitude of incoming workers, and the superiority of the firm they are coming from in terms of productivity.…”
Section: Resultssupporting
confidence: 93%
“…However, according to the extant literature, it is far from trivial that the productivity gap effect is universally present regardless from the structure of the labor market. One counterexample is Germany where Stockinger and Wolf (2016) found no evidence for the productivity gap effect. Therefore, it is important to test the theory in an economy with different level of development and historical context from Denmark where the original model was developed (Stoyanov & Zubanov, 2012).…”
Section: Productivity Gapmentioning
confidence: 99%